
2个回答
展开全部
原式=-(x^4-2x²+1-4x²)
=-[(x²-1)²-4x²]
=-(x²+2x-1)(x²-2x-1)
=-(x²+2x+1-2)(x²-2x+1-2)
=-[(x+1)²-2][(x-1)²-2]
=你给的结果
=-[(x²-1)²-4x²]
=-(x²+2x-1)(x²-2x-1)
=-(x²+2x+1-2)(x²-2x+1-2)
=-[(x+1)²-2][(x-1)²-2]
=你给的结果
展开全部
因式分解
-x^4+6x^2-1
解,得:
==-(x^4-6x^2+1)
==-[(x^2-1)^2-4x^2]
==4x^2-(x^2-1)^2
==[2x+(x^2-1)]*[2x-(x^2-1)]
==(2x+x^2-1)(2x-x^2+1)
解,得:
==[x+(根号2+1)]*[x-(根号2+1)]*[x+(根号2-1)]*[x-(根号2-1)]
==[x^2-(根号2+1)^2]*[x^2-(根号2-1)^2]
==[x^2-(根号2+1)^2]^2
-x^4+6x^2-1
解,得:
==-(x^4-6x^2+1)
==-[(x^2-1)^2-4x^2]
==4x^2-(x^2-1)^2
==[2x+(x^2-1)]*[2x-(x^2-1)]
==(2x+x^2-1)(2x-x^2+1)
解,得:
==[x+(根号2+1)]*[x-(根号2+1)]*[x+(根号2-1)]*[x-(根号2-1)]
==[x^2-(根号2+1)^2]*[x^2-(根号2-1)^2]
==[x^2-(根号2+1)^2]^2
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询